Contextually Aware Agile Security in the Future of Systems Engineering. Issue 1 (30th September 2020) - Dove, Rick; Willett, Keith D.
Abstract: A recurring principle in consideration of the future of systems engineering is continual dynamic adaptation . Context drives change whether it be from potential loss (threats, vulnerabilities) or from potential gain (opportunity‐driven). Contextual‐awareness has great influence over the future of systems engineering and of systems security. Those contextual environments contain fitness functions that will naturally select compatible approaches and filter out the incompatible, with prejudice. This paper provides archetypes that 1) characterize general systems engineering for products, processes, and operations; 2) characterize the integration of security with systems engineering; and, 3) characterize contextually aware agile security. The purpose of this paper is to provide a conceptual understanding of the problem space and derive general security strategies necessary to deal with that problem space, with the intent to provide an initial foundation for subsequent tactical implementations of agile security approaches.